An Integrated Model of Justice and Ethical Climates and the Influence of Cultural Diversity. (2nd April 2015) - Macklin, Robert; Martin, Angela; Mathison, Karin
ABSTRACT The business ethics literature has paid little attention to the similarities, differences, and interactions between 'justice climate' and 'ethical work climate', two key perspectives on the moral dimension of organizations that are related to cultural diversity. In this conceptual paper we argue that integrative studies of justice and ethical work climates could contribute significantly to our understanding of the moral dimensions of organizations. We propose a model showing that an organization's moral climate can perform both normative and evaluative functions. With the globalization of business and increasing diversification of the labour force, cross-cultural differences regarding organizational perceptions and behaviours are increasingly salient. Hence, we also explore the influence of cultural diversity in our integrated model with the Chinese business context as a specific example. We conclude by discussing directions for further research on the relationship between cultural diversity and moral climate in organizations.